2006
DOI: 10.1021/jo0604181
|View full text |Cite
|
Sign up to set email alerts
|

BF3·2CF3CH2OH (BF3·2TFE), an Efficient Superacidic Catalyst for Some Organic Synthetic Transformations

Abstract: BF3.2CF3CH2OH complex was found to be a very effective superacidic catalyst comparable in acid strength to at least that of 100% anhydrous sulfuric acid for various acid-catalyzed organic transformations such as isomerizations, rearrangements, ionic hydrogenation of various ketones, and aromatics with triethylsilane and nitration of aromatics with metal nitrate. Studies of the pivalaldehyde-methyl isopropyl ketone rearrangement and the benzopinacol to phenanthrene transformation suggest that the complex has an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Some early computational work (aimed at benchmarking and validation) included F 2 as test molecule, which proved to be challenging [26][27][28]. Interest in modeling 19 F shifts has steadily continued, and several papers have appeared in the last decade aimed at general structural issues, solution chemistry and physical organic chemistry, [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] solid-state issues (especially the prediction of chemical shift tensors), [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] J-couplings [65][66][67][68][69][70][71][72]…”
Section: Introductionmentioning
confidence: 99%
“…Some early computational work (aimed at benchmarking and validation) included F 2 as test molecule, which proved to be challenging [26][27][28]. Interest in modeling 19 F shifts has steadily continued, and several papers have appeared in the last decade aimed at general structural issues, solution chemistry and physical organic chemistry, [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] solid-state issues (especially the prediction of chemical shift tensors), [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] J-couplings [65][66][67][68][69][70][71][72]…”
Section: Introductionmentioning
confidence: 99%
“…[6] However, synthetic methods to afford these building blocks are very limited, and they often involve multistep synthesis. [7] For example, triarylacetic acid derivatives were often prepared by the reaction of CO 2 and organolithium compounds derived from triarylmethyl chlorides, which were obtained from the corresponding a-triaryl-substituted tertiary alcohols. [6b] Therefore, the development of efficient methods for the diverse synthesis of these compounds is highly desirable.As part of a program directed at the catalytic construction of tetrasubstituted carbon centers using easily available starting materials and catalysts, [8] we were interested in the elaboration of tertiary a-functionalized alcohols.…”
mentioning
confidence: 99%
“…The reactive intermediates are likely to be Cprotonated complexes (when aluminum halides are used) or the O,C-protonated analogs (in triflic acid-SbF 5 ). 889 R = tert-Bu, Bn, Ph 2 CH, Ph 3 481 and cyclohexane in the presence of triflic acid-SbF 5 (Scheme 5.93) 298 are capable of transforming the carbonyl group to methylene group. Mechanistic studies with cyclohexane-d 12 showed that deuterium incorporation takes place exclusively at C (20 0 Ionic hydrogenation can be used to reduce alcohols and it is a convenient way to transform carbonyl compounds to the corresponding methylene derivatives.…”
Section: ð5:323þmentioning
confidence: 99%
“…Aromatics (acenaphthylene, anthracene, benz[a]anthracene, dibenz[a,h]anthracene) can also be reduced with Et 3 SiH-BF 3 -2CF 3 CH 2 OH 481. Aromatics (acenaphthylene, anthracene, benz[a]anthracene, dibenz[a,h]anthracene) can also be reduced with Et 3 SiH-BF 3 -2CF 3 CH 2 OH 481.…”
mentioning
confidence: 99%